2013
DOI: 10.1038/nature12675
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive CD71+ erythroid cells compromise neonatal host defence against infection

Abstract: Newborn infants are highly susceptible to infection. This defect in host defence has generally been ascribed to the immaturity of neonatal immune cells; however, the degree of hyporesponsiveness is highly variable and depends on the stimulation conditions1–7. These discordant responses illustrate the need for a more unified explanation for why immunity is compromised in neonates. Here we show that physiologically enriched CD71+ erythroid cells in neonatal mice and human cord blood have distinctive immunosuppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

38
429
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 353 publications
(472 citation statements)
references
References 30 publications
38
429
2
3
Order By: Relevance
“…Recent data has revealed an important immune regulatory role for erythrocytes. These authors suggested that CD71+ nucleated red blood cells (nRBCs) actively suppress both innate and adaptive immune responses through the expression of arginase, which inhibits nitric oxide synthesis [72]. However, this conclusion was disputed by others whose data suggested that the heightened intestinal immune activation in mice treated with anti-CD71 to deplete the nRBCs was unaffected by replenishment of these cells [73].…”
Section: Mechanisms Of Immune Cell Maturation and Function During Ontmentioning
confidence: 76%
“…Recent data has revealed an important immune regulatory role for erythrocytes. These authors suggested that CD71+ nucleated red blood cells (nRBCs) actively suppress both innate and adaptive immune responses through the expression of arginase, which inhibits nitric oxide synthesis [72]. However, this conclusion was disputed by others whose data suggested that the heightened intestinal immune activation in mice treated with anti-CD71 to deplete the nRBCs was unaffected by replenishment of these cells [73].…”
Section: Mechanisms Of Immune Cell Maturation and Function During Ontmentioning
confidence: 76%
“…Large clinical studies testing associations between functional MIF polymorphisms and MIF expression levels with susceptibility to or severity of neonatal sepsis are now required to substantiate whether MIF represents a potential attractive target for immune-modulating adjunctive therapies for neonatal sepsis. Adding to the recent studies challenging the idea that the neonatal immune system is purely immature (71)(72)(73)(74)(75), the recognition of a unique role for MIF in regulating innate immunity supports the concept that neonatal immune responses are tightly regulated by a balance of pro-and antiinflammatory mediators.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, CD71 + erythroid cells have been shown to suppress the inflammatory response of neonatal murine macrophages by a mechanism involving arginase activity [33]. Other authors postulated that a lack of T cells contributes to the excessive inflammatory response of neonatal splenocytes [34].…”
Section: Discussionmentioning
confidence: 99%